2013
DOI: 10.1021/jm4013246
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the First M5-Selective and CNS Penetrant Negative Allosteric Modulator (NAM) of a Muscarinic Acetylcholine Receptor: (S)-9b-(4-Chlorophenyl)-1-(3,4-difluorobenzoyl)-2,3-dihydro-1H-imidazo[2,1-a]isoindol-5(9bH)-one (ML375)

Abstract: A functional high throughput screen and subsequent multi-dimensional, iterative parallel synthesis effort identified the first muscarinic acetylcholine receptor (mAChR) negative allosteric modulator (NAM) selective for the M5 subtype. ML375 is a highly selective M5 NAM with sub-micromolar potency (human M5 IC50 = 300 nM, rat M5 IC50 = 790 nM, M1–4 IC50 >30 μM), excellent multi-species PK, high CNS penetration, and enantiospecific inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 17 publications
2
78
0
Order By: Relevance
“…Recent screening and medicinal chemistry efforts have resulted in the first subtype-selective small-molecule positive and negative allosteric modulators of muscarinic M 5 mAChRs (Bridges et al, 2010;Gentry et al, 2013Gentry et al, , 2014). ML380 has been described as a PAM of ACh-stimulated calcium mobilization at both human and rat muscarinic M 5 mAChRs, with moderate selectivity versus the M 1 and M 3 mAChR subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent screening and medicinal chemistry efforts have resulted in the first subtype-selective small-molecule positive and negative allosteric modulators of muscarinic M 5 mAChRs (Bridges et al, 2010;Gentry et al, 2013Gentry et al, , 2014). ML380 has been described as a PAM of ACh-stimulated calcium mobilization at both human and rat muscarinic M 5 mAChRs, with moderate selectivity versus the M 1 and M 3 mAChR subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Radioligand-binding studies also suggested that ML380 could increase the affinity of ACh for the M 5 mAChR . ML375 is a highly subtype-selective NAM of ACh-stimulated calcium mobilization at both human and rat muscarinic M 5 mAChRs, which was shown to be allosteric by its ability to slow [ 3 H]-NMS dissociation from the receptor (Gentry et al, 2013). Despite these data, relatively little is known about the mechanisms of modulation by these allosteric ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were also used as anticancer agents, antibiotics, antibacterial agents, and so on [4][5][6][7]. Moreover, they also acted as a useful intermediate in the synthesis of compounds with special properties [8,9]. Dichloroacetyl diazabicyclo derivatives were reported as novel herbicide safener protecting crops from injury by chlorine acetamide herbicides, sulfonylurea herbicides, and imidazolinone herbicides since BASF employed 5-dichloroacetyl-3,3,6-trimethyl-9-oxo-1,5-diazabicyclo[4.3.0] nonane as safeners which increased the toleration of crops to acetanilides herbicides [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…20 A limited chemical optimization effort afforded ML375 ( 2 ), the first M 5 -selective NAM with favorable CNS exposure (brain:plasma K p = 1.8), moderate PK, high plasma protein binding (rat f u = 0.029, human f u = 0.013, rat brain f u = 0.003) and enantiospecific activity (only the ( S )-enantiomer of the 9b p -Cl phenyl wasactive). 20 Despite a major advance in the field, due to weak potency at rat M 5 , coupled with high plasma protein and brain homogenate binding, ML375 lacked the requisite free drug exposure to serve as an in vivo tool compound. 20 In this Letter, we report on the continued optimization of our first-in-class M 5 NAM, and detail key tactics and noteworthy challenges en route to an M 5 NAM in vivo probe.…”
mentioning
confidence: 99%